2018
DOI: 10.1596/1813-9450-8583
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Segregation and Declining Gender Wage Gap: The Case of Georgia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These attributes had been there before 2008. Sectoral segregation is another factor linked to the gender wage gap and the glass ceiling in transition countries (Fang & Sakellariou, 2015; Khitarishvili, 2016; 2018; Pastore & Verashchagina, 2011). The industry difference may be another reason for the glass ceiling in Mongolia.…”
Section: Discussionmentioning
confidence: 99%
“…These attributes had been there before 2008. Sectoral segregation is another factor linked to the gender wage gap and the glass ceiling in transition countries (Fang & Sakellariou, 2015; Khitarishvili, 2016; 2018; Pastore & Verashchagina, 2011). The industry difference may be another reason for the glass ceiling in Mongolia.…”
Section: Discussionmentioning
confidence: 99%
“…Employment is one area where gender-blind and sensitive practices—in hiring, firing, pay, benefits and promotions—implicitly favour men and devalue women. In low- and middle-income countries, men are more likely to be formally employed and occupy higher paying jobs such as those in agriculture, mining, manufacturing and construction ( Khitarishvili et al , 2018 ; Bonnet et al , 2019 ) leading to higher employment stability, and higher short- and long-term wages for men compared with women. Moreover, systematic lack of supports for women’s greater caregiving duties and childbearing activities leads to women working fewer hours than men, often at lower hourly wages, and experiences of permanent income disadvantages when childbearing begins in low-, middle- and high-income countries alike ( Ortiz-Ospina and Roser, 2019 ).…”
Section: Covid-19 and The Employment Sector: A Gendered Analysismentioning
confidence: 99%
“…Yet more explanation is added if demographic factors, such as marital status, the presence of children and aged dependents in the household are added. The degree of industrial and occupational segregation in the labour market has also been found to be a significant determinant of the wage gap in a number of countries (Khitarishvili et al 2018). Overall, Leythienne and Ronkowski (2018) find that just under a third of the 17% gender gap in hourly earnings in the EU could be explained with such an augmented specification.…”
Section: What Do We Know About the Determinants Of The Gender Wage Gap?mentioning
confidence: 99%